Screening of Endophytic Bacteria from Purwoceng Roots (Pimpinella pruatjan Molk.) Antibacterial Activity Against Staphylococcus aureus - GP, Sartika (Journal of Biological Science and Education, 2021)
Most antimicrobial agents, antifungus or antibacterial have been isolated from plants. Purwoceng (Pimpinella pruatjan Molk.) is one of the potential plants that produced an antibacterial agent. But, the status of purwoceng as an endemic plaint in Central Java is "endangered". The endophytic bacteria of the roots can produce an antibacterial agent. The research was performed by purified the endophytic bacteria isolate, the antagonism test as an antibacterial against Staphylococcus aureus also performed, and the data obtained were analyzed descriptively Keywords: Endophytic Bacteria, Pimpinella pruatjan Molk., Staphylococcus aureus